If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -4 * -2 = 10 Multiply -4 * -2 2y + 8 = 10 Reorder the terms: 8 + 2y = 10 Solving 8 + 2y = 10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2y = 10 + -8 Combine like terms: 8 + -8 = 0 0 + 2y = 10 + -8 2y = 10 + -8 Combine like terms: 10 + -8 = 2 2y = 2 Divide each side by '2'. y = 1 Simplifying y = 1
| -42=-6(z-3) | | 5x+9=82-8x | | -3k^2g-[4kg^2-(6k^2g-2kg^2)]=0 | | 3x-3y+3=2 | | Log(3t+1)=5 | | 49=17(t+1) | | 14abc-[3ab^2c+(4a^2bc)-(-3ab^2c-5abc+5a^2bc)]=0 | | -3y+3=2 | | 3.8=m+9.7 | | -3y+3=0 | | 14abc-[3ab^2+(4a^2bc)-(-3ab^2c-5abc+5a^2bc)]=0 | | -3y-3=0 | | E-5=-13 | | 2-s=9 | | 9x^3-729=0 | | 5x-15+3x=5+8x-20 | | 4n^2-4n=0 | | 5(3x-3)+5x=6x+25-x | | x^2-11x-432=0 | | 9x+5=-3x+5+12x | | 3x+1=3x+9 | | S+9=13 | | 8u=-96 | | 3x^2-2xy=8y | | (4m^3-10m^2+2m+3)+(5m^3+3m^2-4m-7)=0 | | A-(-4)=9 | | 2(x+4)=4x-(2x+4) | | 8=n-4.9 | | N+(-3)=-6 | | M-38=76 | | 4pq-6pqr= | | 0.01x=3000-y |